Self-assembly of acetylated dextran with various acetylation degrees in aqueous solutions: Studied by light scattering. (1st March 2017) - Dueramae, Isala; Yoneyama, Masaru; Shinyashiki, Naoki; Yagihara, Shin; Kita, Rio
Highlights: Dextran can self-assemble in water when modified with acetylated groups. Self-assembly of acetylated dextran (Ac-DEXs) is monitored by light scattering method. Molecular weight and radius of gyration of dextran increase with acetylation degree. The aggregates of Ac-DEXs show hard spherical nanoparticles. The highest acetylated substitution represents the formation of gel nanoparticles. Abstract: Self-assembly of acetylated dextran (Ac-DEXs) was investigated with a modified dextran with acetic anhydride in the presence of pyridine. The effect of acetylation degree on solution properties has been investigated by static and dynamic light scattering (DLS). Molecular weight ( M w ) and the radius of gyration ( R g ) of dextran significantly increased with acetylation degree due to the aggregates formation. However, those aggregates noticeably reduced with further increase of acetylation degree. It suggested that the aggregates have shrinkage. The aggregate formation is clearly confirmed by DLS analysis in the presence of the bimodal relaxation distribution for Ac-DEXs. The hydrodynamic radius ( R h ) of fast and slow mode is distinctly corresponded with single dextran macromolecules and aggregates, respectively. The R h of aggregates varied slightly with increasing acetylation degree. The aggregates of Ac-DEXs represent hard spherical nanoparticles whereas the random coil structure is found in dextran. Formation of gel nanoparticles was monitored at the highest acetylated substitution.